CURRENT POSSIBILITIES OF MAGNETIC – RESONANCE IMAGING IN DETECTION OF OVARIAN CANCER - N. A. Rubtsova; E. G. Novikova; I. Yu. Sychenkova (Исследования и практика в медицине, 2017)
Currently, malignant tumors of ovaries take the third place in the structure of oncogynecological diseases, being a leading cause of death among pathology of female reproductive system. Due to the lack of effective screening programs and asymptomatic course of the disease in its early stages, in the majority of cases ovarian cancer (OC) is detected in form of disseminated process, what greatly reduces the effectiveness of primary treatment and has a negative impact on the further prognosis. In connection with the above, timely diagnosis and organization of OC screening, as well as monitoring of its recurrence is a major problem for oncologists around the world.In the present literature review the opportunities of magnetic — resonance imaging (MRI) in detection of primary ovarian cancer and its recurrence are considered, the analysis of the method diagnostic efficiency based on the use of various techniques is done. The opportunities of MRI show a lot of information necessary for the characterization of detected ovarian formations, estimates of the prevalence of primary ovarian cancer and its recurrence. However, the analysis of performed literature revealed a significant lack of materials devoted to the definition of the diagnostic capabilities of various MRI techniques, including diffusion — weighted imaging (DWI), what indicates the necessity for further studies in this direction.